Inovasi Pelayanan Publik Selama Pandemi Covid-19 dsi Provinsi Sumatera Barat - Mahzum, Muhammad; Dzikri, Muhammad Afdhalu (Universitas Labuhanbatu, 2025)
Public services are also one of the areas affected by Covid-19, so that state officials who have been carrying out public services so far must comply with health protocols in providing public services to the community. This study aims to find out how far public service innovation has progressed during the Covid-19 pandemic in West Sumatra Province. The research method used is a qualitative method with a literature study approach from several journals obtained at Google Scholar. From the results of a literature study conducted, it was found that several cities/regencies in West Sumatra Province have carried out innovations in public services, such as Online Population Document Services (PADUKO), ADO Services (Always Ado Pharmacists) and Online Attendance by the Padang City Government.